Modeling and Analysis of the Wastewater Treatment Plant Operating Costs Based on Oxidation Ditch Process - Chen, Liai; Hou, Hongxun; Wang, Jiaquan (Asian Journal of Chemistry, 2013)
In order to further research the influence factors of total costs and reduce power consumption of wastewater treatment plants, based on the long-term operation data of one wastewater treatment plant, the wastewater treatment costs structure and the operation costs influence factors were analyzed. Combining with the mechanism of biological wastewater treatment, the mathematical model that representing wastewater treatment costs as well as sludge disposal costs was deduced and the statistics test verified its usability. The results demonstrated that: (1) the key factors which effected plant total costs were power consumption and sludge disposal costs; (2) Unit power consumption was approximately proportional to sludge retention time within a certain range; (3) Within a flow range of design, the marginal operating costs would reduce as the increasing of sewage quality in sewage treatment plant; (4) The mathematical model of the relationship between sewage treatment costs and power consumption and sludge disposal costs was established. It indicates that we should adopt a large amount of aeration high sludge retention time, thus the sludge will stabilize in the aeration tank when the electricity was in valley. On the contrary, lower aeration rate and lower sludge retention time will be adopted to achieve the lowest total costs of processing when the electricity was in peak.